PEMBELAJARAN BAHASA ARAB BERBASIS HIGHER ORDER THINKING SKILLS (HOTS) DALAM MEMBENTUK PEMBELAJAR YANG KOMPETEN - Aziz, Arif Malik; Atmajaya, Firdaus; Yusuf, Arizal Winanda; Hermawan, Acep (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2024)
The Arabic language learning based on Higher Order Thinking Skills (HOTS) is an innovative approach aimed at developing high-level thinking skills in learners in understanding, interpreting, and using the Arabic language. The objective of this research is to determine what HOTS is, the urgency of HOTS in learning, the methods of implementing HOTS, and the challenges and solutions in its application. This paper uses qualitative research and literature analysis as the data collection technique. The results and discussions of this paper indicate that, in addition to improving language skills, this approach also helps in developing students' self-directed learning. They are encouraged to be active learners capable of constructing arguments, evaluating information, and solving problems with Arabic language intelligence. This approach not only focuses on the technical aspects of language but also provides a deep understanding of the social and cultural context that enriches students' communication skills. However, in the analysis of questions tested on learners, especially at the junior high school level, questions based on HOTS are very rare, sometimes only one or two. Therefore, the researcher hopes that this paper will have an impact on the improvement of the development and implementation of Arabic language learning based on HOTS.